The impact of events scale-revised (IES-R): Validation of the Ukrainian version - Liudmyla Krupelnytska; Nazar Yatsenko; Vladyslava Keller; Olha Morozova-Larina (Comprehensive Psychiatry)
Background: The aftermath of warfare in Ukraine has witnessed traumatic experiences emerge as a significant concern. This highlights the need for strengthened secondary prevention strategies targeting trauma and stress-related disorders. Providing mental health professionals with tools to support refugees is crucial. The Impact of Events Scale – Revised (IES-R) stands out as the prevalent early diagnostic and clinical assessment tool for measuring the traumatic stress symptoms. However, this questionnaire has yet to be psychometrically adapted to the Ukrainian linguistic and cultural context. Objective: This study sought to verify the reliability and validity of the Ukrainian version of the Impact of Events Scale – Revised for adult Ukrainian refugees. Method: A psychometric evaluation was conducted within broader longitudinal research on refugee mental health. The study incorporated a convenience sample of 584 Ukrainian refugees located in Germany. The Ukrainian IES-R's factorial structure underwent validation using CFA with the DWLS estimator. Internal consistency was ascertained using both Cronbach's α and MacDonald's ω. The convergent and divergent validity of the questionnaire were established through Pearson's correlation coefficient. The DIF analysis evaluated diagnostic disparities between groups of respondents identifying as women and men. The ICC, derived from a two-way mixed ANOVA model, and Pearson's correlation coefficients were employed to gauge the test-retest reliability of the IES-R over an 8-month interval between the two data collection waves. Results: The Ukrainian version of the IES-R retains a three-factor, classification-free structure, with a modification of item No. 12 being shifted to the Hyperarousal subscale. Confirmatory metrics (CMIN/DF = 2.874, RMSEA = 0.049, SRMR = 0.065, CFI = 0.977, TLI = 0.974) bolster the model's fit. Consistency coefficients (α, ω) for each subscale ranged from 0.75 to 0.84, with the IES-R's overall values being ω = 0.92 and α = 0.91. The IES-R total score and individual factor values displayed significant (moderate to high) correlations with PSS-10 and either weak or inverse correlations with SWLS, TIPI, and ZTPI-S, aligning with expectations. The test-retest measures showed low temporal stability with an ICC of 0.206 for the total score and a moderate correlation (r = 0.412, p < 0.01), indicating the questionnaire assesses trauma and stressor-related symptoms rather than underlying traits. Conclusion: The data reveal the IES-R as an efficacious diagnostic tool to discern trauma-induced distress in adult Ukrainian refugees. Given its robust psychometric properties, the IES-R is relevant for screening wartime impact.